PESAN DAKWAH DALAM MEME - Muhammad Assof; Teddy Dyatmika (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
There are many forms of da'wah that humans can do to others. Da'wah is no longer standing in front of the pulpit but da'wah can be done at any time using different media. One of the da'wah that can be done by using memes. The researcher analyzed the da'wah in the memes on the fanspage of Islamic da'wah memes. The research method in this research is qualitative using semiotic analysis of Roland Barthes. The source of the research is the memes on the fanspage of Islamic da'wah memes posted in January 2021 as many as 9 posts. The results of this study are that the meme illustrations used by Islamic da'wah meme accounts have an interest in spreading da'wah messages and providing lessons to the public with a unique and creative display of memes that contain Islamic teachings.